谢谢。我已经搞定了。
提供给大家计算公式
y_3:=(923*s1.YValue[i-3]+6*s1.YValue[i-2]-15*s1.YValue[i-1]+20*s1.YValue-15*s1.YValue[i+1]+6*s1.YValue[i+2]-s1.YValue[i+3])/924;
y_2:=(6*s1.YValue[i-3]+888*s1.YValue[i-2]+90*s1.YValue[i-1]-120*s1.YValue+90*s1.YValue[i+1]-36*s1.YValue[i+2]+6*s1.YValue[i+3])/924;
y_1:=(-15*s1.YValue[i-3]+90*s1.YValue[i-2]+699*s1.YValue[i-1]+300*s1.YValue-255*s1.YValue[i+1]+90*s1.YValue[i+2]-15*s1.YValue[i+3])/924;
y3:=(-1*s1.YValue[i-3]+6*s1.YValue[i-2]-15*s1.YValue[i-1]+20*s1.YValue-15*s1.YValue[i+1]+6*s1.YValue[i+2]+923*s1.YValue[i+3])/924;
y2:=(6*s1.YValue[i-3]-36*s1.YValue[i-2]+90*s1.YValue[i-1]-120*s1.YValue+90*s1.YValue[i+1]+888*s1.YValue[i+2]+6*s1.YValue[i+3])/924;
y1:=(-15*s1.YValue[i-3]+90*s1.YValue[i-2]-225*s1.YValue[i-1]+300*s1.YValue+699*s1.YValue[i+1]+90*s1.YValue[i+2]-15*s1.YValue[i+3])/924;
y0:= (20*s1.YValue[i-3]-120*s1.YValue[i-2]+300*s1.YValue[i-1]+524*s1.YValue+300*s1.YValue[i+1]-120*s1.YValue[i+2]+20*s1.YValue[i+3])/924;